Effects of EPI on nutrition of under-five children In rural Bangladesh: the Matlab experience - Ahmed, Syed Masud; Bhuiya, Abbas; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
Objectives: This study was done to explore the effect of immunization (as specified in EPI) on under-five children's nutritional status in a rural area of Bangladesh. Methods: The data for this study originated from a sub-sample of a baseline survey conducted in 60 DSS villages of Matlab thana during 1992. :MUAC, height and weight of 992 children between the age of one to five years were measured using standard technique and socioeconomic information were collected from their mothers using a set of pre-tested structured questionnaire. The level '-2 Z score ' was taken as the cut-off point for "stunting" and the value of less than 125 mm of MUAC for "severely malnourished" children. Results: Both bi-variate and multi-variate analyses revealed the significant role of immunization status in affecting less severe acute malnutrition (NillAC) in poor households which was not seen in the better-off households. Again, immunization status appeared not to have any effect on 'stunting' i.e., long-term nutrition. Wnen considering long-term nutrition (Ht/age), both bi-variate and multi-variate analyses identified mother's education and number of dwellings in the household to be significant influencing factors for the BRAC eligible children. Also, completely immunized children from BRAC non-eligible households were found to have significantly better anthropometric indices than their counterparts . . .<\nother interesting finding was the sex difference seen among the better-off households. Girls in these households were much less likely to be completely immunized, and more likely to be acutely malnourished. This issue needs further exploration for a better understanding of the households' gender dynamics. Conclusions: EPI immunization has some beneficial, if only margina~ impact on the acute nutritional status of the poor children only. It has no effect on chronic nutrition, for which socioeconomic factors seems to play a greater role. Differences exist across socioeconomic status of the household and sex of the children.